Modeling out-migration from depressed regions: the significance of origin and destination characteristics - Clark, G; Ballard, K (Pion Ltd., 1980)
Many migration models, whether derived from the Hicksian macroadjustment approach or from human capital theory, use simultaneously origin and destination variables in their empirical testing procedures. In this paper it is hypothesized that the actual out-migration decision process has two separate but interrelated stages -- the decision to leave and the decision as to the destination. A two-stage estimation procedure is used to analyze the significance of origin characteristics as determinants of out-migration, and the factors that allocate migrants to particular destinations. The model is applied to understanding the patterns and determinants of out-migration from a depressed region, the Central Appalachians of the United States of America. Time-series and cross-sectional models are utilized to evaluate the hypothesized two-stage process over the period 1958 - 1975.